High-pressure-resistant ether polymer electrolyte, solid-state battery and preparation method of high-pressure-resistant ether polymer electrolyte

By using high-pressure-resistant ether polymer electrolytes in lithium-ion batteries, using alkylene oxide monomers and triglycidyl isocyanurate crosslinking agents to polymerize, combining lithium salts and plasticizers, traditional batteries are solved at high energy The problem of insufficient oxidation stability under density has achieved high energy density and long life lithium metal batteries, suitable for new energy vehicles and energy storage applications.

CN119208720APending Publication Date: 2024-12-27SOUTH CHINA UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411257749.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Traditional lithium-ion batteries have low Coulomb efficiency, poor cycle life and short circuit problems under high energy density requirements, and the oxidation stability of ether polymer electrolytes is not sufficient to match the high voltage nickel-rich ternary positive electrode.

Method used

Using a high-pressure resistant ether polymer electrolyte, polymerization by polymerization of alkylene oxide monomers and triglycidyl isocyanurate triglycidyl ester crosslinking agent, lithium salt and plasticizer are added, and non-lithium salt or lithium salt initiator are combined to prepare Electrolyte with high oxidation stability is produced and cured in situ in the battery cell with a skeleton matrix film.

Benefits of technology

It improves the oxidation stability and mechanical strength of the electrolyte, enhances the stability of the electrode interface, simplifies the preparation process, is suitable for high-energy density lithium metal batteries, is compatible with traditional liquid battery production lines, and meets the needs of new energy vehicles and energy storage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208720A_ABST
    Figure CN119208720A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of solid polymer electrolytes, and discloses a high-pressure-resistant ether polymer electrolyte, a solid-state battery and a preparation method thereof.A functional cross-linking agent triglycidyl isocyanurate is added into an ether polymer electrolyte system, an ultra-stable three-dimensional cross-linked copolymer network is formed in the battery, and the high-pressure-resistant ether polymer electrolyte is obtained; and the oxidation resistance of the ether electrolyte system is improved. In addition, the solid polymer electrolyte is prepared in an alkylene oxide cation ring opening in-situ polymerization mode, an electrode-electrolyte integrated structure is formed, and the electrolyte-electrode interface impedance is greatly reduced. The polyether polymer electrolyte prepared by the invention has relatively high oxidation-resistant stability, can stably operate at a high cut-off voltage of 4.7 V, and has good electrochemical stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solid polymer electrolytes, and in particular relates to a high-voltage resistant ether polymer electrolyte, a solid-state battery and a preparation method thereof. Background Art

[0002] With the rapid development of electric vehicles and large-scale energy storage systems, traditional lithium-ion batteries can no longer meet the rapidly growing demand for energy density. 1-x-y Co x Mn y O2, 1-xy ≥ 0.6) integration is considered to be one of the most effective solutions to improve high energy density, because lithium metal anode has the lowest electrochemical potential (-3.04 V vs standard hydrogen electrode) and the highest theoretical specific capacity (3860 mAh g -1 ), while the high nickel ternary cathode has a high theoretical specific capacity and the ability to operate at high voltage (>4.3V). However, traditional organic electrolytes will continuously react with the lithium metal anode to form an unstable electrode / electrolyte interface. The uneven deposition of lithium ions on the lithium metal negative electrode side can lead to uncontrollable dendrite growth and the formation of dead lithium, resulting in low coulombic efficiency, poor cycle life, and even short circuit.

[0003] The use of solid electrolytes instead of liquid electrolytes provides a more feasible solution for integration with lithium anodes, because solid electrolytes can simultaneously provide sufficient ion transport and reduce parasitic reactions between electrolytes and lithium metal. Solid polymer electrolytes based on in situ polymerization are considered to be the most promising solid electrolytes because they can achieve close interfacial contact and have good compatibility with current battery assembly lines. Polyether electrolytes have the advantages of high room temperature ionic conductivity and good compatibility with lithium metal anodes. However, their poor oxidation stability (<4V) hinders the matching of polyether electrolytes with nickel-rich ternary cathodes. The development of high-voltage resistant ether polymer electrolytes is a difficult problem that needs to be solved urgently in the development of high energy density lithium metal batteries. Summary of the invention

[0004] In order to overcome the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a high-voltage resistant ether polymer electrolyte, a solid-state battery and a preparation method thereof.

[0005] The purpose of the present invention is achieved through the following technical solutions:

[0006] The present invention firstly provides a high-voltage resistant ether polymer electrolyte, comprising a lithium salt, a plasticizer and a polymer, wherein the lithium salt and the plasticizer are dispersed in the polymer; the polymer is obtained by polymerizing an alkylene oxide monomer and a triglycidyl isocyanurate crosslinking agent.

[0007] Furthermore, the amount of the triglycidyl isocyanurate cross-linking agent is 1 to 5 wt% of the mass of the alkylene oxide monomer;

[0008] Furthermore, the volume ratio of the alkylene oxide monomer to the plasticizer is 1:1 to 4:1;

[0009] Furthermore, the alkylene oxide monomer is selected from one or more of 1,3-dioxolane, 1,3-dioxane, and tetrahydrofuran.

[0010] Further, the alkylene oxide monomer is dehydrated with a molecular sieve;

[0011] Furthermore, the molecular sieve removes water for a period of 12 to 48 hours.

[0012] Furthermore, the plasticizer is selected from one or more of ethylene carbonate, propylene carbonate, fluoroethylene carbonate, and ethylene glycol dimethyl ether; the plasticizer is a low-viscosity solvent that reduces the crystallinity of the polymer electrolyte and enhances the movement of polymer chain segments.

[0013] Further, the plasticizer is dehydrated with a molecular sieve;

[0014] Furthermore, the molecular sieve removes water for a period of 12 to 48 hours.

[0015] Furthermore, the concentration of the lithium salt relative to the total amount of the alkylene oxide monomer and the plasticizer is 0.6 to 2 mol L -1 ;

[0016] Further, the lithium salt is selected from one or more of lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium perchlorate, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate), lithium tetrafluoroborate, and lithium difluorooxalatoborate;

[0017] Furthermore, the high-voltage resistant ether polymer electrolyte further comprises an initiator;

[0018] Furthermore, the initiator is a non-lithium salt initiator or a lithium salt initiator; the amount of the non-lithium salt initiator is 0.2-1 wt% of the mass of the alkylene oxide monomer, and the concentration of the lithium salt initiator relative to the total amount of the alkylene oxide monomer and the plasticizer is 0.5-1 mol L -1 ;

[0019] Furthermore, the initiator is a Lewis acid initiator;

[0020] Furthermore, the non-lithium salt initiator is selected from one or more of Al(OTf)3 and Sn(Oct)2; the lithium salt initiator is selected from one or more of lithium iodide, lithium hexafluorophosphate, and lithium difluorooxalatoborate.

[0021] Furthermore, the high-voltage resistant ether polymer electrolyte further comprises a skeleton matrix membrane;

[0022] Furthermore, the skeleton matrix membrane is selected from one of polyethylene membrane, polypropylene membrane, lignocellulose membrane, glass fiber membrane, polyimide electrospun membrane, polyvinylidene fluoride electrospun membrane and polyacrylonitrile electrospun membrane.

[0023] The present invention further provides a method for preparing the above-mentioned high-voltage resistant ether polymer electrolyte, comprising the following steps:

[0024] An initiator, triglycidyl isocyanurate cross-linking agent, alkylene oxide monomer, plasticizer and lithium salt are uniformly mixed to obtain a precursor solution, and the precursor solution is heated and solidified to obtain a high-voltage resistant ether polymer electrolyte.

[0025] Further, the volume ratio of the alkylene oxide monomer to the plasticizer is 1:1 to 4:1;

[0026] Furthermore, the heating curing temperature is 50-70°C and the time is 10-18h;

[0027] Furthermore, the preparation method is carried out in a dry and protective atmosphere; the O2 in the environment is less than 0.1 ppm, and the H2O is less than 0.1 ppm.

[0028] Furthermore, the precursor solution is configured as follows:

[0029] The lithium salt is dissolved in the plasticizer, triglycidyl isocyanurate crosslinking agent is added, and then the initiator is added, and stirred for 24 to 36 hours to obtain a uniform mixed solution; the mixed solution is mixed and stirred with the alkylene oxide monomer for 2 to 4 hours to obtain a precursor solution.

[0030] The present invention also provides a solid-state battery, comprising a positive electrode, the above-mentioned high-voltage resistant ether polymer electrolyte and a negative electrode.

[0031] Furthermore, the active material of the positive electrode is one of lithium iron phosphate, lithium nickel oxide, lithium cobalt oxide, lithium iron manganese phosphate, lithium manganese oxide, lithium nickel manganese oxide, nickel cobalt manganese ternary positive electrode, and sulfur positive electrode; the material of the negative electrode is lithium metal.

[0032] The present invention finally provides a method for preparing the above-mentioned solid-state battery, comprising the following steps:

[0033] The precursor solution of the high-voltage resistant ether polymer electrolyte is injected into the battery cell and allowed to stand for 10 to 18 hours under heating conditions to obtain a solid-state battery; the precursor solution of the high-voltage resistant ether polymer electrolyte comprises an initiator, a triglycidyl isocyanurate cross-linking agent, an alkylene oxide monomer, a plasticizer and a lithium salt; the battery cell comprises a positive electrode, a skeleton matrix film and a negative electrode; the amount of the precursor solution is per 1 cm 2 Add 30-60 μL of precursor solution to the skeleton matrix membrane.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] First, the present invention removes water from the alkylene oxide monomer and the plasticizer with a molecular sieve, dissolves the lithium salt in the plasticizer; then adds a cross-linking agent containing a special functional group and mixes them evenly; mixes the mixed solution with the alkylene oxide monomer evenly to prepare a precursor solution; injects the precursor solution into the battery cell with the skeleton matrix membrane, and solidifies it in situ at a certain temperature to obtain a high-voltage ether polymer electrolyte. The present invention provides a method for preparing a high-voltage ether polymer electrolyte. On the one hand, the terminal hydroxyl group of the polymer electrolyte is eliminated to prevent the terminal unit from being preferentially oxidized under high voltage; on the other hand, by introducing a high oxidation stability fragment into the polymer body, the oxidation resistance of the electrolyte system is improved, which is conducive to the realization of a high energy density lithium metal battery.

[0036] Second, the technical solution of the present invention can be produced on traditional liquid battery production lines without major changes to the production lines. It has very high compatibility and can accelerate the development of traditional liquid batteries towards high-safety solid-state batteries. It can meet the urgent needs for high-safety, high-specific energy and high-power batteries for new energy vehicles and large-scale energy storage.

[0037] The technical solution of the present invention fills the technical gap in the industry at home and abroad: the present invention provides a new ether polymer electrolyte, which solves the defects of easy oxidation and poor matching with high-voltage cathode in traditional ether electrolyte systems. It is a design method and structural innovation in electrolyte engineering, and provides a solution for the industrialization of high-energy density and high-rate lithium metal batteries.

[0038] Third, the preparation method of the high-voltage resistant ether polymer electrolyte provided by the present invention brings the following significant technical advances:

[0039] (1) Enhanced oxidation stability of the electrolyte: The ether electrolyte prepared by the present invention not only provides good lithium ion transmission performance, but also improves the oxidation stability of the electrolyte, which is crucial for improving the service life and energy density of the battery.

[0040] (2) Simplified preparation process: Through the in-situ curing method, the ether polymer electrolyte is directly formed in the battery cell with the skeleton matrix membrane, which simplifies the complex steps in the traditional electrolyte preparation process and improves production efficiency.

[0041] (3) Enhanced interfacial stability between electrolyte and electrode: Through the in-situ solidification method, an integrated electrode-electrolyte structure is formed directly inside the battery, which greatly reduces the interfacial impedance compared to traditional polymer electrolytes.

[0042] (4) Improved mechanical strength of the electrolyte: The ether polymer electrolyte prepared by the present invention enhances the mechanical strength of the electrolyte, making it more suitable for application in high-performance batteries.

[0043] (5) Wide applicability: This method allows the use of a variety of different types of lithium salts and skeleton matrix membranes, making it widely applicable and adjustable according to specific application requirements.

[0044] The preparation method of the high-voltage resistant ether polymer electrolyte provided by the present invention brings significant technological progress in improving battery performance, simplifying the preparation process and improving safety, and is expected to play an important role in the field of high-performance solid-state batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 is a flow chart of a method for preparing an ether polymer electrolyte provided by an embodiment of the present invention;

[0046] Figure 2 is a photograph of the state transformation of the ether polymer electrolyte precursor solution provided in Example 1 of the present invention after being kept at 60° C. for 12 hours;

[0047] Figure 3 It is a test data diagram of ether polymer electrolyte ion conductivity under different embodiments and comparative example 1 provided in the embodiments of the present invention;

[0048] Figure 4 is a linear sweep voltammetry curve of the ether polymer electrolyte provided in Example 1 of the present invention and Comparative Example 1;

[0049] Figure 5 1 is a graph showing the relationship between the discharge capacity at room temperature and the number of cycles of the nickel-cobalt-manganese 622 battery assembled with the ether polymer electrolyte provided in Example 1 and Comparative Example 1 at a cut-off voltage of 4.5V;

[0050] Figure 6 This is a relationship diagram between the room temperature discharge capacity and the number of cycles of the nickel-cobalt-manganese 622 battery assembled with the ether polymer electrolyte provided in Example 1 at a cut-off voltage of 4.7V. DETAILED DESCRIPTION

[0051] The specific implementation of the present invention is further described below in conjunction with examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. If the manufacturer of the reagents or instruments used is not indicated, they are deemed to be conventional products that can be purchased commercially.

[0052] Example 1

[0053] The preparation method of the ether polymer electrolyte provided by the embodiment of the present invention (reference Figure 1), including the following steps:

[0054] Step 1: First, remove water from the alkylene oxide monomer and plasticizer required in the experimental scheme using molecular sieves for 24 hours.

[0055] Step 2: In a dry glove box filled with argon (O2<0.1ppm, H2O<0.1ppm), 0.6 mol L -1 (relative to the alkylene oxide monomer and the plasticizer) lithium bis(trifluoromethylsulfonyl)imide was dissolved in 25 parts by volume of the plasticizer fluoroethylene carbonate, 5 wt% (relative to the alkylene oxide monomer) triglycidyl isocyanurate was added, and 0.6 mol L -1 (relative to the alkylene oxide monomer and the plasticizer) lithium difluorooxalate borate, stirred for 24 h to obtain a uniform mixed solution.

[0056] Step 3: The prepared mixed solution was mixed with 75 parts by volume of 1,3-dioxolane (DOL), an alkylene oxide monomer, and stirred for 2 hours to obtain a final ether polymer electrolyte precursor solution.

[0057] Step 4: Inject the final precursor solution into the cell with polypropylene film, and add 1 cm per 1 cm of the substrate film area. 2 30 μL was added to the mixture, and the mixture was kept at 60°C for 12 hours to obtain an ether polymer electrolyte battery cell. The positive electrode of the battery cell was a nickel-cobalt-manganese 622 ternary positive electrode, and the negative electrode was lithium metal. In addition, during the electrochemical data testing, a similar battery assembly method was used, with only the electrodes being different.

[0058] Example 2

[0059] The preparation method of the ether polymer electrolyte provided by the embodiment of the present invention (reference Figure 1 ), including the following steps:

[0060] Step 1: First, remove water from the alkylene oxide monomer and plasticizer required in the experimental scheme using molecular sieves for 24 hours.

[0061] Step 2: In a dry glove box filled with argon (O2 < 0.1 ppm, H2O < 0.1 ppm), 1 mol L -1 Lithium bis(trifluoromethylsulfonyl)imide was dissolved in 25 parts by volume of the plasticizer fluoroethylene carbonate (relative to the alkylene oxide monomer), 5 wt% (relative to the alkylene oxide monomer) triglycidyl isocyanurate was added, and 0.5 mol L -1 (relative to the alkylene oxide monomer and the plasticizer) lithium hexafluorophosphate, stirred for 24 hours to obtain a uniform mixed solution.

[0062] Step 3: The prepared mixed solution was mixed with 75 parts by volume of 1,3-dioxolane (DOL), an alkylene oxide monomer, and stirred for 2 hours to obtain a final ether polymer electrolyte precursor solution.

[0063] Step 4: Inject the final precursor solution into the cell with polypropylene film, and add 1 cm per 1 cm of the substrate film area. 2 30 μL was added to the mixture, and the mixture was kept at 60°C for 12 hours to obtain an ether polymer electrolyte battery cell. The positive electrode of the battery cell was a nickel-cobalt-manganese 622 ternary positive electrode, and the negative electrode was lithium metal. In addition, during the electrochemical data testing, a similar battery assembly method was used, with only the electrodes being different.

[0064] Example 3

[0065] The preparation method of the ether polymer electrolyte provided by the embodiment of the present invention (reference Figure 1 ), including the following steps:

[0066] Step 1: First, remove water from the alkylene oxide monomer and plasticizer required in the experimental scheme using molecular sieves for 24 hours.

[0067] Step 2: In a dry glove box filled with argon (O2 < 0.1 ppm, H2O < 0.1 ppm), 1 mol L -1 Lithium bis(trifluoromethylsulfonyl)imide was dissolved in 25 parts by volume of the plasticizer fluoroethylene carbonate (relative to the alkylene oxide monomer), 5 wt% (relative to the alkylene oxide monomer) triglycidyl isocyanurate was added, and 0.5 mol L -1 (relative to the alkylene oxide monomer and the plasticizer) lithium hexafluorophosphate, stirred for 24 hours to obtain a uniform mixed solution.

[0068] Step 3: The prepared mixed solution was mixed with 75 parts by volume of 1,3-dioxolane (DOL), an alkylene oxide monomer, and stirred for 2 hours to obtain a final ether polymer electrolyte precursor solution.

[0069] Step 4: Inject the final precursor solution into the cell with the polyvinylidene fluoride ceramic membrane, and add 1 cm2 of the substrate membrane area. 2 30 μL was added to the mixture, and the mixture was kept at 60°C for 12 hours to obtain an ether polymer electrolyte battery cell. The positive electrode of the battery cell was a nickel-cobalt-manganese 622 ternary positive electrode, and the negative electrode was lithium metal. In addition, during the electrochemical data testing, a similar battery assembly method was used, with only the electrodes being different.

[0070] Example 4

[0071] The preparation method of the ether polymer electrolyte provided by the embodiment of the present invention (reference Figure 1 ), including the following steps:

[0072] Step 1: First, remove water from the alkylene oxide monomer and plasticizer required in the experimental scheme using molecular sieves for 24 hours.

[0073] Step 2: In a dry glove box filled with argon (O2 < 0.1 ppm, H2O < 0.1 ppm), 1 mol L -1 (relative to the alkylene oxide monomer and plasticizer) lithium bis(trifluoromethylsulfonyl)imide was dissolved in 25 parts by volume of the plasticizer ethylene glycol dimethyl ether, 5 wt% (relative to the alkylene oxide monomer) triglycidyl isocyanurate was added, and 0.5 mol L -1 (relative to the alkylene oxide monomer and the plasticizer) lithium hexafluorophosphate, stirred for 24 hours to obtain a uniform mixed solution.

[0074] Step 3: The prepared mixed solution was mixed with 75 parts by volume of 1,3-dioxolane (DOL), an alkylene oxide monomer, and stirred for 2 hours to obtain a final ether polymer electrolyte precursor solution.

[0075] Step 4: Inject the final precursor solution into the cell with polypropylene film, and add 1 cm per 1 cm of the substrate film area. 2 30 μL was added to the mixture, and the mixture was kept at 60°C for 12 hours to obtain an ether polymer electrolyte battery cell. The positive electrode of the battery cell was a nickel-cobalt-manganese 622 ternary positive electrode, and the negative electrode was lithium metal. In addition, during the electrochemical data testing, a similar battery assembly method was used, with only the electrodes being different.

[0076] Comparative Example 1

[0077] The preparation method of this comparative example comprises the following steps (refer to Figure 1 ):

[0078] Step 1: First, remove water from the alkylene oxide monomer and plasticizer required in the experimental scheme using molecular sieves for 24 hours.

[0079] Step 2: In a dry glove box filled with argon (O2<0.1ppm, H2O<0.1ppm), 0.6 mol L -1 (relative to the alkylene oxide monomer and the plasticizer) lithium bis(trifluoromethylsulfonyl)imide was dissolved in 25 parts by volume of the plasticizer fluoroethylene carbonate, 5 wt% (relative to the alkylene oxide monomer) trimethylolpropane triglycidyl ether was added, and 0.6 mol L -1 (relative to the alkylene oxide monomer and the plasticizer) lithium difluorooxalate borate, stirred for 24 h to obtain a uniform mixed solution.

[0080] Step 3: The prepared mixed solution was mixed with 75 parts by volume of 1,3-dioxolane (DOL), an alkylene oxide monomer, and stirred for 2 hours to obtain a final ether polymer electrolyte precursor solution.

[0081] Step 4: Inject the final precursor solution into the cell with polypropylene film, and add 1 cm per 1 cm of the substrate film area. 2 30 μL was added to the mixture, and the mixture was kept at 60°C for 12 hours to obtain an ether polymer electrolyte battery cell. The positive electrode of the battery cell was a nickel-cobalt-manganese 622 ternary positive electrode, and the negative electrode was lithium metal. In addition, during the electrochemical data testing, a similar battery assembly method was used, with only the electrodes being different.

[0082] Performance Testing:

[0083] The ether polymer electrolyte precursor solution provided in Example 1 was kept at 60° C. for 12 h. The photographs of the state transition before and after the keeping are shown in FIG. Figure 2 , showing the macroscopic transformation of the initial ether polymer electrolyte precursor solution to a non-fluid ether polymer electrolyte, providing evidence for the effective polymerization of Example 1.

[0084] Figure 3 By comparing the electrochemical impedance spectra of the ether polymer electrolytes provided in different embodiments and comparative examples in the SS / / SS symmetric battery, it can be seen that the ether polymer electrolyte using triglycidyl isocyanurate as a cross-linking agent has a lower impedance.

[0085] The linear sweep voltammetric curves of the ether polymer electrolyte provided in Example 1 and Comparative Example 1 in the Li / / SS battery are as follows: Figure 4 , it can be seen that the oxidation potential of Example 1 is 5.10V, and the oxidation potential of Comparative Example 1 is 4.45V.

[0086] The relationship between the discharge capacity and the number of cycles of the Li / / NiCoMn 622 battery assembled with the ether polymer electrolyte provided in Example 1 and Comparative Example 1 at room temperature with a cut-off voltage of 4.5V is shown in the figure: Figure 5 The first discharge specific capacity (1C) of the Li / / nickel-cobalt-manganese 622 battery obtained in Example 1 is 175.4 mAh / g, and the capacity retention rate after 450 cycles is 81.2%. The first discharge specific capacity (1C) of the Li / / nickel-cobalt-manganese 622 battery obtained in Comparative Example 1 is 161.7 mAh / g, and the capacity retention rate after 450 cycles is 7.9%.

[0087] The relationship between the discharge capacity and the number of cycles of the Li / / NiCoMn 622 battery assembled with the ether polymer electrolyte provided in Example 1 at room temperature with a cut-off voltage of 4.7V is as follows: Figure 6 The first discharge specific capacity (1C) of the Li / / nickel-cobalt-manganese 622 battery obtained in Example 1 is 192.4 mAh / g, and the capacity retention rate after 400 cycles is 81.8%.

[0088] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.

Claims

1. A high-voltage resistant ether polymer electrolyte, characterized in that: The invention comprises lithium salt, plasticizer and polymer, wherein the lithium salt and the plasticizer are dispersed in the polymer; the polymer is obtained by polymerizing an alkylene oxide monomer and a triglycidyl isocyanurate crosslinking agent.

2. The high-voltage resistant ether polymer electrolyte according to claim 1, characterized in that: The amount of the triglycidyl isocyanurate cross-linking agent is 1 to 5 wt% of the mass of the alkylene oxide monomer; The volume ratio of the alkylene oxide monomer to the plasticizer is 1:1 to 4:1; The alkylene oxide monomer is selected from one or more of 1,3-dioxolane, 1,3-dioxane, and tetrahydrofuran; The alkylene oxide monomer is dehydrated by using a molecular sieve; the time for dehydration by using the molecular sieve is 12 to 48 hours.

3. The high-voltage resistant ether polymer electrolyte according to claim 1, characterized in that: The plasticizer is selected from one or more of ethylene carbonate, propylene carbonate, fluoroethylene carbonate, and ethylene glycol dimethyl ether; The plasticizer is dehydrated by molecular sieve; the time for dehydration by molecular sieve is 12 to 48 hours.

4. The high-voltage resistant ether polymer electrolyte according to claim 1, characterized in that: The concentration of the lithium salt relative to the total amount of the alkylene oxide monomer and the plasticizer is 0.6 to 2 mol L -1 ; The lithium salt is selected from one or more of lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium perchlorate, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate), lithium tetrafluoroborate, and lithium difluorooxalatoborate.

5. The high-voltage resistant ether polymer electrolyte according to claim 1, characterized in that: The high-voltage resistant ether polymer electrolyte further includes an initiator; The initiator is a non-lithium salt initiator or a lithium salt initiator; the amount of the non-lithium salt initiator is 0.2-1 wt% of the mass of the alkylene oxide monomer, and the concentration of the lithium salt initiator relative to the total amount of the alkylene oxide monomer and the plasticizer is 0.5-1 mol L -1 ; The initiator is a Lewis acid initiator; The non-lithium salt initiator is selected from one or more of Al(OTf)3 and Sn(Oct)2; the lithium salt initiator is selected from one or more of lithium iodide, lithium hexafluorophosphate, and lithium difluorooxalatoborate.

6. The high-voltage resistant ether polymer electrolyte according to claim 1, characterized in that: The high-voltage resistant ether polymer electrolyte further comprises a skeleton matrix membrane; The skeleton matrix membrane is selected from one of polyethylene membrane, polypropylene membrane, wood cellulose membrane, glass fiber membrane, polyimide electrospun membrane, polyvinylidene fluoride electrospun membrane and polyacrylonitrile electrospun membrane.

7. The method for preparing the high-voltage resistant ether polymer electrolyte according to any one of claims 1 to 6, characterized in that: The following steps are involved: The initiator, triglycidyl isocyanurate cross-linking agent, alkylene oxide monomer, plasticizer and lithium salt are uniformly mixed to obtain a precursor solution, and the precursor solution is heated and cured to obtain a high-voltage resistant ether polymer electrolyte; The heating curing temperature is 50-70°C and the time is 10-18h; The preparation method is carried out in a dry and protective atmosphere; the O2 in the environment is less than 0.1 ppm, and the H2O is less than 0.1 ppm.

8. A solid-state battery, characterized in that: The invention comprises a positive electrode, the high-voltage-resistant ether polymer electrolyte according to any one of claims 1 to 6, and a negative electrode.

9. The solid-state battery according to claim 8, characterized in that: The active material of the positive electrode is one of lithium iron phosphate, lithium nickel oxide, lithium cobalt oxide, lithium iron manganese phosphate, lithium manganese oxide, lithium nickel manganese oxide, nickel cobalt manganese ternary positive electrode, and sulfur positive electrode; the material of the negative electrode is lithium metal.

10. The method for preparing a solid-state battery according to any one of claims 8 to 9, characterized in that: The following steps are involved: The precursor solution of the high-voltage resistant ether polymer electrolyte is injected into the battery cell and allowed to stand for 10 to 18 hours under heating conditions to obtain a solid-state battery; the precursor solution of the high-voltage resistant ether polymer electrolyte comprises an initiator, a triglycidyl isocyanurate cross-linking agent, an alkylene oxide monomer, a plasticizer and a lithium salt; the battery cell comprises a positive electrode, a skeleton matrix film and a negative electrode; the amount of the precursor solution is per 1 cm 2 Add 30-60 μL of precursor solution to the skeleton matrix membrane.

Citation Information

Patent Citations

  • In-situ cross-linking polymerization solid electrolyte and preparation method and application thereof

    CN116706223A

  • Solid polymer electrolyte, preparation method and solid-state battery

    CN117393849A